Antiviral therapy and prophylaxis of acute respiratory infections - L. V. Osidak; E. G. Golovacheva; E. A. Dondurey; O. I. Afanasyeva; E. V. Obraztsova; V. P. Drinevsky; E. S. Goncharova; V. F. Suhovetskaya; K. K. Milkint (LLC "Diagnostics and Vaccines", 2016)
Thearticle presents the results of years of studies (including biochemical and immunological) of the effectiveness of application and prophylaxis (in relation to nosocomial infections) and the safety of antiviral chemical preparation Arbidol in 694 children with influenza and influenza-like illness, including the coronavirus infection (43 children) and combined lesions of respiratory tract (150), indicating the possible inclusion of the drug in the complex therapy for children with the listed diseases, regardless of the severity and nature of their course. The studies were conducted according to the regulated standard of test conditions and randomized clinical trials.